The use of endogenous retroviruses as markers to describe the genetic relationships among local Swedish sheep breeds. (23rd January 2015) - Mukiibi, R.; Rochus, C. M.; Andersson, G.; Johansson, A. M.
Summary The aim of this study was to describe the genetic relationships among five Swedish sheep breeds using insertional polymorphisms of six endogenous Jaagsiekte retroviruses of sheep. Although the Swedish breeds were found to have genomes of 'primitive' origin, there also are indications of the presence of more recently derived sheep breeds within the ancestries of three of the breeds.